Narrative Review: Optimization of AI-Based HR Management System for Remuneration and Performance Equity in Hospitals - Hartono, Enrico Jonathan (Asosiasi Ahli Administrasi Indonesia, 2025)
Human resource management (HRM) in Indonesian hospitals faces significant challenges in ensuring fairness, transparency and objectivity in performance evaluation and remuneration systems. These issues contribute to income disparities between medical and managerial staff, leading to lowered morale and reduced quality of healthcare services. This study aims to provide an existing performance appraisal system, identify remuneration inequities, and propose an AI-based meritocracy model to improve transparency and accountability. Through a systematic literature review of global and local sources, the study identifies objective key performance indicators (KPIs) and develops an AI-based conceptual framework for equitable distribution of remuneration, drawing on successful practices from countries such as the UK and Singapore. The proposed model integrates AI technologies such as machine learning and predictive analytics to optimize recruitment, performance monitoring and incentive allocation while addressing ethical concerns such as algorithmic bias and data privacy. This AI-based approach aims to increase healthcare worker motivation, reduce turnover, and improve service quality in Indonesian hospitals, with recommendations for phased implementation and strong governance to ensure ethical implementation.